Creation of the universal system of dynamic control of emissions of diesel solid particles on the basis of microtunnel - Polivyanchuk, A. P.; Kaslin, O. I.; Smirny, M. F.; StrokovO. Р.; Skuridina, O. O. (Man and Environment. Issues of Neoecology, 2017)
Purpose. Creation of a national universal system of dynamic control of particulate emissions from diesel engines of different types – automobile, diesel, tractor, court and others on the basis of the measuring complex with the microtunnel MKT-2. Methods. Analysis and synthesis of information, mathematical modeling, calculated experiment. Results. The modern dynamic methods of control of emissions of diesel particulate matter are analyzed: Method for Real-Time Mass Microbalance, Tapered Element Elemental Microscopic Microbalance – TEOM, Quartz Crystal Microbalance – QCM and Laser Induced Incandescence – LII, their technical characteristics are determined. A schematic diagram of a dynamic method for controlling emissions of solid particles with an optical sensitive element has been developed. A procedure has been developed for determining the permissible degree of dilution of diesel exhaust gases by air in the tunnel. Conclusions. The technical capabilities of the microtunnel MKT-2 for environmental diagnostics of various engines have been determined. The recommendations on the creation of a universal system for the ecological diagnosis of transport diesels based on MKT-2 have been substantiated. It has been established ranges of variation of the dilution coefficients of exhaust gases in the tunnel are established for testing diesel engines corresponding to various norms of the Euro. The necessity of using a gas sample cooler in a tunnel is verified when controlling the concentration of solid diesel particles meeting the requirements of Euro-6 standards.